Impact of El Niño and La Niña on Precipitation and Temperature Patterns in Nigerian Regions: A Case Study of Lagos and Port-Harcourt - Olawale, K. O.; Adetunji, E.O. (Darul Yasin Al Sys, 2024)
This study explores the impact of El Niño and La Niña events on local climate patterns in Nigeria, focusing specifically on the region of Lagos and Port-Harcourt. Utilizing ERA5 reanalysis data, including total precipitation (TP) and 2-meter air temperature (T2m), alongside NOAA ERSST v5 sea surface temperature (SST) anomalies, we investigate the correlations between SST anomalies in the Pacific and Atlantic Oceans and the weather variables in these regions. The objective is to elucidate how these global climate phenomena affect regional weather patterns in West Africa. Our analysis reveals significant alterations in precipitation and temperature patterns during El Niño and La Niña events, with distinct impacts observed in Lagos (a coastal region) and Port-Harcourt (another coastal city). These findings highlight the variability in climatic responses across different regions of Nigeria, depending on the intensity and duration of the events. This research enhances understanding of the mechanisms through which global climate phenomena influence local weather conditions, offering valuable insights for improving climate forecasts and informing effective adaptation strategies. The study contributes to the broader field of climate science by integrating global and regional climate data, emphasizing the importance of such analyses in developing nations for comprehensive weather and climate predictions.